2016
DOI: 10.1016/j.wasman.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Meat waste as feedstock for home composting: Effects on the process and quality of compost

Abstract: Home composting is a powerful tool, which is spreading in different parts of the world, to reduce the generation of municipal waste. However, there is debate concerning the appropriateness, in terms of domestic hygiene and safety, of keeping a composter bin in the household deputed to kitchen waste of animal origin, such as meat or fish scraps and pet droppings. The purpose of our work was to study how the addition of meat scraps to household waste influences the composting process and the quality of the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 32 publications
6
25
0
3
Order By: Relevance
“…Considering that WSC values decreased at the end of the process (see Fig. 5a), pine wood shavings in unsieved samples could have contributed to compost C total content, as it was stated before and observed by Storino et al (2016a and2016b). Thus, it could be assumed that final compost TOC was mainly composed of this more stable C source.…”
Section: Compost Stability Indicators and Quality Monitoring Variablessupporting
confidence: 51%
See 4 more Smart Citations
“…Considering that WSC values decreased at the end of the process (see Fig. 5a), pine wood shavings in unsieved samples could have contributed to compost C total content, as it was stated before and observed by Storino et al (2016a and2016b). Thus, it could be assumed that final compost TOC was mainly composed of this more stable C source.…”
Section: Compost Stability Indicators and Quality Monitoring Variablessupporting
confidence: 51%
“…The C: N ratio (TOC: TKN ratio, in this study) has also been considered as a reference to assess compost stability, and it could be relevant to understand changes in the composting process. However, it is currently a controversial parameter and requires being complemented with other variables and indicators in order to evaluate the stability of a compost, as it is done in this study (Adhikari et al, 2012c;Karnchanawong and Suriyanon, 2011;Storino et al, 2016aStorino et al, , 2016b. Despite this considerations, other authors and environmental authorities have suggested a C: N ratio between 10 and 20 for defining compost stabilization (Mazzarino et al, 2012;Papadopoulos et al, 2009).…”
Section: Compost Stability Indicators and Quality Monitoring Variablesmentioning
confidence: 98%
See 3 more Smart Citations